Fundamentals of Entrepreneurship ETR300 : Sportivo Arena / Andie Ambang… [et al.] - Ambang, Andie; Minggu, Martin Sherman; Muhd Sarip, Mohd Fakhrur Razi; Ahmad, Noraini; Wan Nawang, Wan Norsaidatina Hasma (2011)
The purpose of choosing the business is to serve customers around Kota Samarahan with popular sport such as futsal. This is because the people must have a good fitness level and enjoyment for their life to make sure they have a good life and stay healthy. Our proposal is to help entrepreneur serve as a guideline to the organization in order to accomplish any business's movement. Besides that, it is use to persuade certain party for instance the bank in order to give a business's loan. As a company that based on the services, operational and marketing plan are important for the guidelines how to implement activities and work with competence and increasing the company sale. We are concentrating in Kota Samarahan area about 593.9 KM as target marker.